how do i solve

2(3x+8)=-23+9

2(3x + 8)= -23+92(3x + 8)= -14(3x + 8)= -73x + 8 =`-73x = -15x= -5
mark_c
23 March 2017
Make sure that you work one step at a time, applying the basic rules of algebra at every step. Mark's solution below is an exemplary solution, there are other ways you could do it which would get the same solution.
Iain W.
23 March 2017
2(3x+8)=-23+9or, 6x+16=-14or, 6x=-14-16=-30or, x=-30/5=-6
soumyo
23 March 2017
IMG_20170323_183952.jpg
Shivam D.
23 March 2017
Hi there,So this problem requires you to find the value of x. To do this, first add the 9 to the -23. You should get:2 (3x + 8) = -14Then, multiply out the bracket - so times everything within the bracket by the 2 on the outside. This will leave you with;6x + 16 = -14Now you should take 16 away from both sides of the equation in order to keep it balanced. Hence you will have:6x = -30The final step is to divide both sides of the equation by 6, leaving you with:x = -5
william_philpot
23 March 2017
20170325_153755.jpg
Jayesh A.
25 March 2017
patricktoulson
26 March 2017
2(3x+8) = 23+9or 6x+16=32or 6x=16or x = 16/6=2.67
carajusn
28 March 2017
2(3x+8) = -23+9goes to:6x + 16 = -23+9 (because you multiply 2 and 3x together to get 6x, and 2 and 8 together to get 16)This goes to:6x + 16 = -14 (-23 + 9 is the same as 9 - 23, which equals -14)This goes to:6x = -30 (you minus 16 from both sides - you're allowed to do this because it's the same to both sides)This goes to:x = -5 (because you divde both sides by 6)Ta Da! Hope this helps.
Charlie H.
28 March 2017
Step 1: Simplify both sides of the equation            -23 + 9 = -14            2 (3x + 8) = 6x + 16            Therefore 6x + 16 = -14Step 2: Collect all the terms of "x" on one side, and all of the numbers on the other. In this case this is done by subtracting 16 from both sides         (6x + 16) - 16 = -14 - 16         -->   6x = -30Step 3: Further simplify to find the value of x. In this case by dividing both side of the equation by 6          6x/6 = -30/6       --> x = -5
Natalie B.
29 March 2017
-5
moushitamahmud
31 March 2017
6x + 16 = -146x = -14 -166x = -30x = -30/6 = -5
denner1991
02 April 2017
6x + 16 = -146x = -14 -166x = -30x = -30/6 = -5
denner1991
02 April 2017
6x + 16 = -146x = -14 -166x = -30x = -30/6 = -5
denner1991
02 April 2017
Expand the brackets and then it becomes a lot easier
atzhan2001
04 April 2017
when u multiply 2 in brackets then u obtain 6x+16=-146x=-14-16 6x=-30divide 6 on both sidesx=-5
umerhayat
09 April 2017
Step 1. Divide both sides of the equation by 2:2/2(3x+8)=(-23+9)/2=> 3x+8=-14/2=> 3x+8=-7Step 2. Substract 8 from both sides3x+8-8=-7-8=>3x=-15Step 3. Divide both sides by 33x/3=-15/3=> x=-5
guillezago
19 May 2017
4
Tayonga
16 September 2020